2019
DOI: 10.14710/joac.3.3.132-141
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan kualitas planlet tanaman pisang raja bulu (Musa paradisiaca) dengan penambahan bap dan iaa pada media pengakaran kultur in vitro

Abstract: Penelitian ini bertujuan untuk mengkaji pengaruh penambahan BAP dan IAA pada media pengakaran kultur jaringan terhadap pertumbuhan tanaman pisang raja bulu (Musa paradisiaca). Penelitian dilaksanakan di Laboratorium Kultur Jaringan Kebun Benih Hortikultura Salaman, Magelang pada bulan Juni hingga Agustus 2018. Rancangan penelitian yang digunakan adalah Rancangan Acak Lengkap (RAL) faktorial dengan 4 (empat) kali ulangan. Faktor pertama adalah hormon BAP dengan konsentrasi masing-masing 0 ; 0,5 ; 1 ; 1,5 ; dan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The treatment of BAP 5 mg L -1 + IAA 0.1 mg L -1 and BAP 5 mg L -1 + IAA 0.5 mg L -1 showed average shoot length 1.25-1.51 cm at 5 th and 7 th WAI (Table 5). A similar study was shown [10] that the treatment of 22 M BAP (4.96 mg L -1 ) + 2 M IAA (0.35 mg L -1 ) resulted in the longest average shoot length. The shoot elongation of the Barangan Merah cultivar explants was better in the combination treatment of BAP and IAA compared to the giving of single BAP.…”
Section: The Average Shoot Length Per Explantsupporting
confidence: 70%
See 2 more Smart Citations
“…The treatment of BAP 5 mg L -1 + IAA 0.1 mg L -1 and BAP 5 mg L -1 + IAA 0.5 mg L -1 showed average shoot length 1.25-1.51 cm at 5 th and 7 th WAI (Table 5). A similar study was shown [10] that the treatment of 22 M BAP (4.96 mg L -1 ) + 2 M IAA (0.35 mg L -1 ) resulted in the longest average shoot length. The shoot elongation of the Barangan Merah cultivar explants was better in the combination treatment of BAP and IAA compared to the giving of single BAP.…”
Section: The Average Shoot Length Per Explantsupporting
confidence: 70%
“…The combination treatment of BAP and IAA on different cultivars resulted in different growth responses. This was shown in combination of BAP 1 mg L -1 and IAA 3mg L -1 resulted the best explant growth for Raja Bulu cultivars [10].…”
Section: The Average Shoot Length Per Explantmentioning
confidence: 75%
See 1 more Smart Citation
“…The plant that can be used as a source of explant is derived from the leaves, roots, bud eyes, pollen, stem ends, and bulbs maintained sterile. Factors that influence success in tissue culture are genotypes, culture media, growing environments, and explants (Nofiyanto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%